A student guide to object-oriented development - Britton, Carol, 1947-; Doake, Jill, 1946- (Amsterdam ; London : Elsevier Butterworth-Heinemann, 2005)
This is an introductory text that follows the software development process, from requirements capture to implementation, using an object-oriented approach. The book uses object-oriented techniques to present a practical viewpoint on developing software, providing the reader with a basic understanding of object-oriented concepts by developing the subject in an uncomplicated and easy-to-follow manner. It outlines standard object-oriented modelling techniques and illustrates them with a variety of examples and exercises, using UML as the modelling language and Java as the language of implementation. The book is based on a main worked case study for teaching purposes, plus others with password-protected answers on the web for use in coursework or exams. * Adopts a simple, step by step approach to object-oriented development * Includes case studies, examples, and exercises with solutions to consolidate learning * Benefit from the authors' years of teaching experience.
Preface; List of trademarks; Chapter 1 -- Introduction; Chapter 2 -- Frameworks and Approaches; Chapter 3 -- Requirements; Chapter 4 -- Use cases and scenarios; Chapter 5 -- The Class Diagram; Chapter 6 -- Sequence and collaboration diagrams; Chapter 7 -- State diagrams; Chapter 8 -- Activity diagrams; Chapter 9 -- Design techniques; Chapter 10 -- Implementation diagrams; Chapter 11 -- Implementation; Chapter 12 -- Testing; Chapter 13 -- Putting it all together; Bibliography; Glossary; Answers to selected exercises; Index.
Includes bibliographical references and index.
Keywords: Object-oriented methods (Computer science).; Computer software -- Development; Electronic books